The Leading Impact Journal in Dermatopathology - Gürkan Kaya (MDPI AG, 2024)
As the Editor-in-Chief of Dermatopathology and the President of the European Society of Dermatopathology (ESDP), I have the great pleasure of celebrating the 10th anniversary of Dermatopathology, the only online journal in the field of cutaneous pathology and the official journal of the ESDP [...]